The Role of Peridotite and Serpentinite in the Deep Carbon Cycle: Constraints from Ophiolites and Exhumed Metamorphic Terranes - Menzel, Manuel D. (Universidad de Granada, 2019)
The main aim of the present Ph.D. thesis is to improve our understanding of carbonation processes of serpentinized peridotite and the fate of serpentinite-hosted carbon during highpressure metamorphism, in order to better constrain their role in the deep carbon cycle of subduction zones. To advance in this overall research goal, this Ph.D. thesis presents the results of two natural case studies of key processes of carbon transfer during fluid-rock interaction in subduction zones: (i) listvenites from the Baie Verte ophiolite (Newfoundland, Canada), a natural analogue for carbon storage in the forearc mantle of subduction zones by carbonation of peridotites; and (ii) meta-ophicarbonates from the Nevado-Filábride Complex (Spain), which provide unprecedented insights into the stability of carbonates during antigorite-serpentinite dehydration in a paleo-subduction terrane. The combination of field, (micro) structural, petrological and geochemical data with thermodynamic modelling sheds new light on the interaction of fluids with the hydrated mantle, which regulates the carbon mobility at forearc and subarc depths of subduction zones. By means of thermodynamic models of prograde and high-pressure infiltration-driven devolatilization reactions in serpentinite-hosted meta-carbonate rocks, this thesis further investigates the effects of electrolytic fluids and the role of open-system flux by serpentinite dehydration fluids on the fluid-mediated release of carbon in subduction zones. [ES] El principal objetivo de la presente tesis doctoral es el de mejorar nuestra comprensión de los procesos de carbonatación de peridotitas serpentinizadas y el destino del carbono alojado en las serpentinitas durante el metamorfismo de alta presión; la finalidad ultima de este estudio es contribuir a un mejor entendimiento del papel que juegan estos procesos en el ciclo profundo del carbono en las zonas de subducción. Para avanzar en este objetivo general de investigación, en esta tesis se presentan los resultados de estudios de ...